2019
DOI: 10.1103/physrevb.100.104420
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale mechanisms for magnetostriction in CoFe2O4 and La0.5

Abstract: The atomic environments involved in the magnetostriction effect in CoFe 2 O 4 and La 0.5 Sr 0.5 CoO 3 polycrystalline samples have been identified by differential extended x-ray absorption fine structure (DiffEXAFS) spectroscopy. We demonstrate that cobalt atoms at octahedral sites are responsible for their magnetostriction. The analysis of DiffEXAFS data indicates that the local-site magnetostrictive strains of Co atoms are reversed in these two oxides, in agreement with the macroscopic magnetostriction. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As the 3d-orbitals are coupled to the lattice via crystal field interaction, the lattice expands along the field direction. Very recently, Subi ́as et al 52 carried out differential X-ray absorption in La 0.5 Sr 0.5 CoO 3 and CoFe 2 O 4 with and without an external magnetic field and concluded that the Co−O bond length along the [100] axis elongates under a magnetic field in La 0.5 Sr 0.5 CoO 3 , whereas it shrinks in CoFe 2 O 4 . The elongation is consistent with the observation we made here.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the 3d-orbitals are coupled to the lattice via crystal field interaction, the lattice expands along the field direction. Very recently, Subi ́as et al 52 carried out differential X-ray absorption in La 0.5 Sr 0.5 CoO 3 and CoFe 2 O 4 with and without an external magnetic field and concluded that the Co−O bond length along the [100] axis elongates under a magnetic field in La 0.5 Sr 0.5 CoO 3 , whereas it shrinks in CoFe 2 O 4 . The elongation is consistent with the observation we made here.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was assumed in Ref.9 that this band is related to electronic transitions from the valence band into the VО+3d(Fe 3+ ) state, where VО denotes an oxygen vacancy. However, it was recently shown 25 that the oxygen environment of the Co 2+ and Fe 3+ ions experiences octahedral distortions, which are stronger in the case of Co 2+ . We can assume that the band (1) is formed by the transitions into the VО+3d(Fe 3+ ) or/and VО+3d(Co 2+ ) states.…”
Section: Absorption Spectrummentioning
confidence: 99%
“…5 Exploration of magnetotransport in hole-doped rare-earth cobaltites other than R=La did not evoke much enthusiasm among researchers because the magnitude of MR at T=TC decreases with decreasing size of R 3+ or divalent alkaline earth ions. 6,7,8,9 An intriguing property of cobaltites is the existence of giant anisotropic magnetostriction in La1-xSrxCoO3 series (x=0.3-0.5) attributed to magnetic field-induced spin-state transition of Co ions at low temperatures, 10,11,12 however, magnetostriction in other rare-earth cobaltites is scarcely reported until now. 13,14 In this letter, we report the influence of Co-site substitution on the magnetization, magnetoresistance and magnetostriction in Pr0.6Sr0.4Co1-yGayO3 (y=0-0.3).…”
mentioning
confidence: 99%